Artificial Intelligence and the Two Singularities - Chace, Calum (Boca Raton, FL : CRC Press, 2018)
"The science of AI was born a little over 60 years ago, and since then, AI systems have obeyed Moores Law, doubling in processing power roughly every 18 months. They have surpassed human ability in image recognition, and are catching up with us at speech recognition and natural language processing. Every day, the media reports the launch of a new service, a new product, and a new demonstration powered by AI. When will it end? The surprising truth is, the AI revolution has hardly begun.Artificial Intelligence and the Two Singularities argues that through the course of this century, the exponential growth in the capability of AI is likely to bring about two "singularities", or points at which conditions are so extreme that the normal rules break down. The first is the economic singularity, when machine skill reaches a point that renders many of us unemployable and will require an overhaul of the current economic system. The second is the technological singularity, when machine intelligence reaches and then surpasses the cognitive abilities of an adult human, reducing us to the second smartest species on the planet. Though the implication of such obstacles is huge, the good news is that we can meet the challenges posed by the two singularities, and overcome them. Even better news is that the reward could potentially be as unimaginable as the perils; we just need to prepare. This book covers: Current developments in AI and the future of AIThe economic singularity and the technological singularity in depthOpportunities provided by AIAI analysis from several points of viewArtificial intelligence can turn out to be the best thing ever to happen to humanity, making our future wonderful almost beyond imagination. But, our future welfare depends on our determination to learn about and meet these problems head on.Calum Chace is a best-selling author of fiction and non-fiction books and articles focusing on the subject of artificial intelligence. He is a regular speaker on artificial intelligence and related technologies, and runs a blog on the subject at www.pandoras-brain.com. Prior to becoming a full-time writer and speaker, he spent 30 years in business as a marketer, a strategy consultant, and a CEO. He studied philosophy at Oxford University, where he discovered that the science fiction he had been reading since boyhood was simply philosophy in fancy dress."--Provided by publisher.
part, Artificial Intelligence / Chace Calum -- chapter Introduction / Chace Calum -- chapter An Overnight Sensation, after 60 Years / Chace Calum -- chapter The State of the Art / Chace Calum -- chapter Exponential Improvement / Chace Calum -- chapter Tomorrow$1 (Bs AI /s Chace Calum -- chapter Singularities / Chace Calum -- part, The Technological Singularity / Chace Calum -- chapter How to Make an Artificial General Intelligence / Chace Calum -- chapter When Might the First AGI Arrive? / Chace Calum -- chapter From AGI to Superintelligence (ASI) / Chace Calum -- chapter Will Superintelligence Be Beneficial? / Chace Calum -- chapter Ensuring that Superintelligence is Friendly (FAI) / Chace Calum -- chapter The Technological Singularity / Chace Calum -- part, The Economic Singularity / Chace Calum -- chapter The History of Automation / Chace Calum -- chapter Is It Different This Time? / Chace Calum -- chapter The Challenges / Chace Calum -- chapter Four Scenarios / Chace Calum -- chapter Protopian Un-forecast / Chace Calum -- chapter The Economic Singularity / Chace Calum -- chapter Outroduction / Chace Calum.
Keywords: Artificial intelligence; Artificial Intelligence; Cognitive Artificial Intelligence; COMPUTERSCIENCEnetBASE; INFORMATIONSCIENCEnetBASE; ITECHnetBASE; SCI-TECHnetBASE; STMnetBASE